High resolution radiosonde measurements from station Ny-Ålesund (2025-08) - Maturilli, Marion (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Potsdam, 2025)
At AWIPEV research base in Ny-Ålesund, Svalbard, regular radiosonde launches are operated once per day. The launch frequency may increase to 6-hourly soundings during specific campaign periods. The Vaisala RS41-SGP radiosondes provide data of pressure, temperature, relative humidity, wind speed and wind direction from ground to about 30 km height. The given data set contains vertical profiles with 1-second time resolution data as obtained by the manufacturer's data processing, quality controlled for appropriate physical ranges.